STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA INDUSTRI SOFTWARE DI INDONESIA - Hayun, Anggara (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
The development of information and telecommunication (IT) industries is very fast in the world, and haves been effected by Indonesian software industry development. The Indonesian software industrial market shares a more growth every year. The growth market demands a readiness of human resource development (HRD). Then, a human resources strategic planning must be needed. Therefore, the human resources strategic planning are hoped to improve human resources development skill, thus software industries have a competitive, advantage not only in local but also in global. Area the result indicates that the strategy conducted to develop human resource in industrial industries are facilities supply and incentive by government in facilities, policy and regulation.